Antibody-suppressor CD8+ T Cells Require CXCR5. Issue 9 (September 2019) - Zimmerer, Jason M.; Ringwald, Bryce A.; Elzein, Steven M.; Avila, Christina L.; Warren, Robert T.; Abdel-Rasoul, Mahmoud; Bumgardner, Ginny L.
Abstract : Background: We previously reported the novel activity of alloprimed CD8 + T cells that suppress posttransplant alloantibody production. The purpose of the study is to investigate the expression and role of CXCR5 on antibody-suppressor CD8 + T-cell function. Methods: C57BL/6 mice were transplanted with FVB/N hepatocytes. Alloprimed CD8 + T cells were retrieved on day 7 from hepatocyte transplant recipients. Unsorted or flow-sorted (CXCR5 + CXCR3 − and CXCR3 + CXCR5 − ) alloprimed CD8 + T-cell subsets were analyzed for in vitro cytotoxicity and capacity to inhibit in vivo alloantibody production following adoptive transfer into C57BL/6 or high alloantibody-producing CD8 knock out (KO) hepatocyte transplant recipients. Alloantibody titer was assessed in CD8 KO mice reconstituted with naive CD8 + T cells retrieved from C57BL/6, CXCR5 KO, or CXCR3 KO mice. Antibody suppression by ovalbumin (OVA)-primed monoclonal OVA-specific t-cell receptor transgenic CD8+ T cells (OT-I) CXCR5 + or CXCR3 + CD8 + T-cell subsets was also investigated. Results: Alloprimed CXCR5 + CXCR3 − CD8 + T cells mediated in vitro cytotoxicity of alloprimed "self" B cells, while CXCR3 + CXCR5 − CD8 + T cells did not. Only flow-sorted alloprimed CXCR5 + CXCR3 − CD8 + T cells (not flow-sorted alloprimed CXCR3 + CXCR5 − CD8 + T cells) suppressed alloantibody production and enhanced graft survival when transferred into transplant recipients. Unlike CD8 + T cells from wild-type or CXCR3 KO mice, CD8 + T cells from CXCR5 KO mice do not develop alloantibody-suppressor function. Similarly, only flow-sorted CXCR5 + CXCR3 − (and not CXCR3 + CXCR5 − ) OVA-primed OT-I CD8 + T cells mediated in vivo suppression of anti-OVA antibody production. Conclusions: These data support the conclusion that expression of CXCR5 by antigen-primed CD8 + T cells is critical for the function of antibody-suppressor CD8 + T cells. Abstract : Supplemental Digital Content is available in the text.